Factors influencing the effectiveness of recombinant human soluble thrombomodulin on disseminated intravascular coagulation: a retrospective study - Yuki Asai; Takanori Yamamoto; Daisuke Kito; Kazuya Ichikawa; Yasuharu Abe (BMC, 2020)
Abstract Background Although recombinant human soluble thrombomodulin (rTM) has been widely used to treat disseminated intravascular coagulation (DIC) in Japan, there is no consensus regarding rTM efficacy. Therefore, if the factors influencing rTM efficacy is revealed, it may be possible to demonstrate the effectiveness of rTM by limiting the patients who use rTM. This study investigated the factors of rTM treatment which influence DIC status. Methods This retrospective case-control study enrolled hospitalized adult patients treated with rTM from October 2010 to May 2020. Among these patients, 227 who were diagnosed with DIC according to the Japanese Association for Acute Medicine DIC scoring system were assessed. The primary endpoint was the 28-day mortality after rTM treatment. For Cox-proportional hazards model, explanatory factors determined using univariate analysis with p <  0.1 were used. In addition, some factors considered to affect DIC-related mortality such as age ≥ 75 years, rTM dose ≥380 U/kg, antithrombin III treatment, and diseases with a poor prognosis (sepsis, solid tumors, and trauma) were added as covariates. Results Univariate analyses suggested that male sex (p = 0.029), treatment in intensive care unit (p = 0.061), and prothrombin time-international normalized ratio (PT-INR) (p <  0.001) were the factors influencing DIC-related 28-day mortality after rTM treatment. According to Cox-proportional hazard analysis, the adjusted odds ratio for DIC-related 28-day mortality in patients with PT-INR ≥ 1.67 was 2.23 (95% confidence interval: 1.451-3.433, p <  0.001), age ≥ 75 years was 1.57 (95% confidence interval: 1.009-2.439, p = 0.046), and male sex was 1.66 (95% confidence interval: 1.065-2.573, p = 0.025), respectively. As life-threatening bleeding events were not observed, prolonged PT-INR might directly or indirectly affect DIC-related mortality caused by rTM treatment. Conclusion rTM treatment for DIC was less effective in male patients with PT-INR ≥ 1.67 and age ≥ 75 years.